2000
DOI: 10.1016/s0895-7061(99)00238-1
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Alcohol Intake and Development of Hypertension in Japanese Normotensive Men: 12-Year Follow-Up Study

Abstract: Although it has been suggested that alcohol intake is related to hypertension, few long-term prospective studies have investigated this relationship. We therefore conducted a prospective study in male residents of a farming community in Japan to determine whether heavy drinking would predispose to the development of hypertension. A total of 325 normotensive (< 140/90 mm Hg) men were enrolled in 1977. Twelve years later, 93 (28.6%) subjects became hypertensive (defined as blood pressure > or = 140/90 mm Hg or u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
1
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 23 publications
4
43
1
3
Order By: Relevance
“…Como cabía esperar, los resultados concuerdan con la hipótesis que establece que un consumo excesivo de alcohol incrementa el riesgo de hipertensión arterial [22][23][24] y respalda las recomendaciones generales sobre la reducción del consumo de alcohol como medida para prevenir la hipertensión arterial 25 .…”
Section: Discussionunclassified
“…Como cabía esperar, los resultados concuerdan con la hipótesis que establece que un consumo excesivo de alcohol incrementa el riesgo de hipertensión arterial [22][23][24] y respalda las recomendaciones generales sobre la reducción del consumo de alcohol como medida para prevenir la hipertensión arterial 25 .…”
Section: Discussionunclassified
“…[62][63][64] Tsuruta et al 62 reported that the probability of the development of hypertension in heavy drinkers (alcohol consumption^46 g per day) was about twice that of the rest of the population after a 12-year follow-up among normotensive men. Fuchs et al 63 showed that the consumption of alcohol at^30 g per day was an independent risk factor among participants in the Atherosclerosis Risk in Communities (ARIC) study.…”
Section: Actions Of Alcohol On Water and Electrolyte Metabolismmentioning
confidence: 99%
“…Alcohol consumption has been associated with the development of hypertension (1)(2)(3)(4)(5)(6)(7)(8)(9)(10), and Japanese men consume more alcoholic beverages than men in many other developed countries, including the United States and the United Kingdom (11)(12)(13)(14)(15). These facts suggest that the high consumption of alcoholic beverages among Japanese men may contribute to the high prevalence of hypertension in Japan (12,16).…”
Section: Introductionmentioning
confidence: 99%